Development and Characterization of a Topically Deliverable Prophylactic Against Oxidative Damage in Cochlear Cells - Arrigali, Elizabeth M.; Serban, Monica A. (Frontiers in Pharmacology, 2022)
Hearing loss affects roughly 466 million people worldwide. While the causes of hearing loss are diverse, mechanistically, inflammation and oxidative stress have been identified as major players in hearing loss regardless of pathogenesis. Treatment options remain extremely limited and there is currently no FDA approved drug therapy. Studies indicate that antioxidants such as D-Methionine have shown some protective effects; however, these studies involved systemic or invasive localized delivery methods and highlighted the need for the development of minimally invasive localized therapeutic approaches. Described herein is the development of an antioxidant-conjugated system that shows prophylactic potential against oxidative damage and appears suitable for topical delivery. Specifically, our covalent conjugate of hyaluronan with D-Methionine shows cytocompatibility and protection from oxidative stress in two mouse cochlear cell lines (HEI-OC1 and SV-k1). Mechanistically, the data indicate that the protective effects of the conjugate are due to the hyaluronan-mediated cellular internalization of the antioxidant. Most notably, the conjugate can efficiently permeate through an in vitro round window membrane model without the loss of the attached antioxidant, for subsequent delivery of the therapeutic cargo to the hearing sensory cells. Collectively these findings show that the novel conjugate could be a potential topical preventive agent against hearing loss.